A new Orussus species from South Korea, and a key to the East Asian Orussidae (Hymenoptera) - Choi, Jin-Kyung; Wei, Meicai; Vilhelmsen, Lars; Lee, Jong-Wook (Zootaxa, 2014)
Orussus melanosoma Lee & Wei, sp. nov. from South Korea is described and illustrated. Phylogenetic analyses place the new species basally in Orussus, together with other species from the Far East. A key to species of Orussidae from the eastern Palaearctic is provided.